High Temperature Corrosion Behaviour of Aluminide-Coated Cast Iron for an Exhaust Manifold Application - Panya Kerdbua; Mohammad Hassan Shirani Bidabadi; Walairat Chandra-ambhorn; Somrerk Chandra-ambhorn (My University, 2020)
To reduce the pollution emission from vehicles, an improvement on the combustion process is expected, leading to increased exhaust gas temperature. As a result, the development of new materials for an exhaust manifold used at higher temperatures is required. A cost-effective cast iron exhaust manifold treated by aluminising pack cementation was developed in the present work to combat the high temperature corrosion. Its kinetics under cyclic oxidation in N2–12%O2–10%H2O at 850 °C was parabolic with the rate constant (kp) of 5.66 × 10−12 g2 cm–4 s–1, about two orders of magnitude lower than that of the bare cast iron, which indicated the protectiveness of the applied coating. These results relate to the protective alumina formation for the aluminised cast iron and the formation of the less protective iron oxides for the bare cast iron after oxidation, as evidenced by the XRD and Raman spectroscopy results. The addition of 10% water vapour to N2–12%O2 thickened the aluminide layer from 344 μm for the sample oxidised in dry atmosphere to 409 μm for the sample oxidised humidified one. It accelerated the oxidation rate of the aluminised cast iron as the kp value increased by 8.5 times, and also increased the hardness of the aluminised surface, as it was 364 HV for the sample exposed to dry atmosphere and 420 HV for the sample exposed to humidified one. The latter result implied the possibility of the hydrogen dissolution into the metal surface. The roles of hydroxyl ion and dissolved hydrogen on the oxidation and evolution of the aluminide layer after exposure to water vapour were proposed.
Keywords: Aluminide; Exhaust manifold; High-Temperature Coating Behaviors